Doktrin Pilihan Allah Dalam Roma 9 Bagi Peneguhan Iman Jemaat - Priyono, Joko (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
The doctrine of God's choice of believers is a concept that is difficult to explain and has become a theological polemic to this day. This concept polemic occurs in groups that emphasize works as the basis of salvation and groups that emphasize grace as the basis of salvation. The Bible explains that the doctrine of choice of believers (predestination) is a very important part, and this doctrine is closely related to the teaching of salvation. Specifically, the Bible explains the doctrine of God's choice of believers in the letter Romans 9. Therefore, the author uses the exegetical method to find the meaning of God's choice of believers as an effort to strengthen the congregation's faith. God chooses His chosen people based on God's covenant, God's purposes, God's generosity, and God's sovereignty. And Allah chooses His chosen people through faith, and not because of good deeds. Faith here is faith in the Lord Jesus who is the center and target of faith.